ความเข้าใจและการจัดการเรียนรู้ธรรมชาติของวิทยาศาสตร์ของครูวิทยาศาสตร์ในโรงเรียนเอกชนสอนศาสนาอิสลามในจังหวัดยะลา - เซฟโฆลาม, โรซวรรณา; ขำวงษ์, พินิจ; พฤกษ์ประมูล, ชนินันท์; ฮายีสาเมาะ, อับดุลนาเซร์ (Al-HIKMAH Journal, 2018)
This research aimed to study science teachers, understanding of Nature of science (NOS) and teaching Nature of Science in the Islamic private schools in Yala province. This research was a qualitative research using Multi-case studies as a research design. The participants were 6 science teachers from three Islamic private schools in Yala province. The research instrument was a semi-structured interview protocol and the data were qualitatively analyzed using analytic induction method. The results of this study revealed that; All science teachers in this study could not explain the meaning of NOS, Moreover, they could not explain clearly about the importance of NOS, for examples, they understood that teaching NOS could help students to learn directly from the environment and some teachers understood that NOS could help students to identify scientific processes. Science teachers in this study understood each aspect of NOS, The aspects that all science teachers in this study had an informed understanding were 1) science can explain the natural phenomena, 2) scientific knowledge can be changed, and 3) scientific knowledge needs empirical and accountable evidence. The aspects that most of science teachers in this study had partially informed understanding were 1) science and technology are related to each other 2) science is based on observation and inference which are different, and 3) society and culture have an influence on the work of scientists. The aspects that most of science teachers in this study had both partially informed understanding and naïve understanding were 1) theories and law are different, and 2) science is based on imagination and creativity. There was one aspect that all science teachers in this study had naïve understanding which was the scientific method composed of various ways and has no fixed procedure. All science teachers in this study had taught NOS using implicit approach. They emphasized on providing experiments and hands-on activities for students, but did not explicitly discuss about NOS related to the lesson. Moreover, they lack of understanding about how to teach NOS in science classroom.